Effects of an intensified competition period on neuromuscular function in youth rugby union players - Tee, J. C.; Till, K.; Jones, B. (Sport Performance & Science Reports, 2017)
P laying rugby union matches causes a number of fatigue responses, including reduced lower body neuromuscular function (NMF) (commonly measured by counter movement jump (CMJ))(1). The time course of this response following match play is well established in professional (2) and academy (3) level rugby union players, who take at least 60 hours for NMF to recover. No data exist for high school level rugby union players, but these players are often exposed to multiple game tournaments and festivals (2 games in 3 days, or 3 games in 5 days) within their competition structures. Aim. The aim of this case study is to document the NMF response to playing three rugby union matches within five days. This will provide useful information to practitioners who must manage fatigue and recovery of youth rugby union players who play multiple games within short time periods.